Case report: Different mechanisms of drug resistance in a synchronous multiple primary lung cancer patient after EGFR-TKI treatment - Xie, Shaonan; Liu, Qingyi (Frontiers in Oncology, 2022)
Non-small-cell lung cancer (NSCLC) is the most common cancer in the world. In recent years, the incidence of synchronous multiple primary lung cancer (SMPLC) has gradually increased. Surgery is the preferred method to treat these patients. The management of SMPLC patients who cannot tolerate surgical treatment is controversial. We report a rare case in which a 70-year-old Chinese woman with no history of smoking had three primary lung adenocarcinoma lesions. Two lesions had epidermal growth factor receptor (EGFR) exon 19 deletion mutations, and one lesion had the L858R mutation. After first-generation EGFR–tyrosine kinase inhibitor (TKI) treatment, the three lesions all showed a good response until disease progression. After the corresponding drug treatments were given based on the different drug resistance mechanisms, good responsiveness was shown in each lessions. This case suggests that in the treatment of SMPLC, it is necessary to learn the molecular-biological information of each lesion due to the differences thereof, and a targeted treatment regimen should be developed on this basis.